1984
DOI: 10.1111/j.1365-2125.1984.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enzyme induction and enzyme inhibition on labetalol pharmacokinetics.

Abstract: The oral and intravenous pharmacokinetics of labetalol were determined in five subjects before and after a 3 week course of glutethimide 500 mg/day. After glutethimide there was a significant reduction in the AUC after the oral dose of labetalol, from 40,596 +/‐ 11,534 (mean +/‐ s.e. mean) to 22,057 +/‐ 6,276 ng ml‐1 min (2P less than 0.05), and systemic bioavailability was reduced from 30.3 +/‐ 2.8 to 17.0 +/‐ 3.5% (2P less than 0.001). There was no significant change in labetalol plasma concentration‐time cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 18 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…A decrease in drug clearance is the likely explanation for these changes, perhaps reflecting auto-inhibition of hepatic drug metabolising capacity. Analogous inhibitory effects have been reported for propranolol (McDevitt, 1988) and for cimetidine which has been shown to inhibit the metabolism of both labetalol (Daneshmend & Roberts, 1984) and also dilevalol, albeit to a lesser extent (Tenero et al, 1989). This study indicates that there is no independent agerelated difference in the antihypertensive response to dilevalol.…”
Section: Side Effects and Visual Analogue Scoressupporting
confidence: 85%
“…A decrease in drug clearance is the likely explanation for these changes, perhaps reflecting auto-inhibition of hepatic drug metabolising capacity. Analogous inhibitory effects have been reported for propranolol (McDevitt, 1988) and for cimetidine which has been shown to inhibit the metabolism of both labetalol (Daneshmend & Roberts, 1984) and also dilevalol, albeit to a lesser extent (Tenero et al, 1989). This study indicates that there is no independent agerelated difference in the antihypertensive response to dilevalol.…”
Section: Side Effects and Visual Analogue Scoressupporting
confidence: 85%
“…It has been shown that cimetidine substantially increased the AUC of labetalol, a drug with systemic clearance approaching hepatic blood flow, after oral administration but not after intravenous administration. 26 Thus if one applies the simplifying assumption that the effect observed for the C,, of saquinavir is primarily caused by suppression of the first-pass metabolism, then doses of 200, 300, and 600 mg ritonavir yielded a 23-, 27-, and 34-fold inhibition of the first-pass metabolism, respectively. If the net effect on AUC is the product of first-pass and postabsorptive inhibition, then the latter corresponding inhibition can be estimated to be 2.2, 2.5, and 3.9-fold, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1984), and it had no effect on the heart rate or forced expiratory volume at 1 second (FEV d in the latter study group. Data on the effects of cimetidine on the kinetics of other ~-blockers are limited; cimetidine reportedly had no effect on the disposition of labetalol (Daneshmend & Roberts 1984), penbutolol or pindolol (Mutschler et al 1984) in healthy volunteers.…”
Section: !I-blockersmentioning
confidence: 97%
“…The resting heart rate and supine blood pressure of 5 volunteers during labetalol treatment were not significantly altered by cimetidine, although labetolol AVC was increased and 1 patient experienced postural hypotension (Daneshmend & Roberts 1984). A summary of drug interactions involving cimetidine and various ~-blockers can be found in table VI.…”
Section: !I-blockersmentioning
confidence: 97%